Comparative study for efficacy of termination in first trimester pregnancy using Misoprostol and Mifepristone - Georgi Stanulov; Xanthi Anthoulaki; Dorelia Deuteraiou; Anna Chalkidou; Grigorios Trypsianis; Werner Rath; Roland Csorba; Georgios Galazios; Panagiotis Tsikouras (Archives of Community Medicine and Public Health - Peertechz Publications, 2018)
Background: The best method for medical abortion depends fundamentally on pregnancy duration and the final result varies on medical stuff's experience. The aim of this study pertained to investigate the effectiveness of medical abortion using misoprostol, mifepristone or the combination of them.  Patients and methods: During the period April 2007 to December 2017, 200 women with pregnancy until 49 days after LMP (last menstrual period) underwent medical termination by using 600 mg mifepristone (RU 486) (Mifegyn) Group A1 per os vs 800 mcg misoprostol (Cytotec) A2 and in other 200 pregnant women, duration between 49-63 days was administrated using 600 mg mifepristone followed 48 hours later 800 mcg misoprostol B1 vaginaly vs. only misoprostol B2. All participants were consistent with surgical abortion if deemed necessary and a transvaginal ultrasound was performed to confirm an intrauterine pregnancy before the medical administration. The indications for the abortion were as following: missed abortion, endometrial death, spontaneous and induced abortions.  Results: According to our study, there was not a case needed to undergo surgical abortion. Common side effects like nausea, vomiting, pain and moderate vaginal bleeding were noticed without the need of hospitalization. Bleeding was occurred earlier in Group A1 compared to Group A2. In addition, abortion started about 3.5 hours earlier in Group A1 compared to Group A2. Similarly, time between administration and abortion was 50% shorter in Group A1 compared to Group A2. The duration of bleeding in Group B1 in Group B2 was similar in the two groups. Analgesia was not necessary for any participant, while repeat administration was more than 7 times more frequent in Group B2 compared to Group B1. Conclusion: The combination of mifepristone and misoprostol and the single administration of mifepristone are safe and effective for medical termination of pregnancy in early first trimester.